Uncertainty and risk during the COVID‐19 pandemic: A latent profile analysis - Johnson, Angela E.; Hua, Jacqueline; Hinojosa, Bianca; Meese, William B.; Gray, Avia; Howell, Jennifer L. (Social and personality psychology compass, 2023)
In the present study, we examine how subgroups of people are characterized by different profiles of uncertainty surrounding COVID‐19, susceptibility, and recovery. Participants ( N  = 199) were U.S. residents recruited online for a longitudinal study during the summer of 2020. We first, identified groups using latent profile analysis (LPA) and then examined whether these profiles predicted differences in COVID‐related risky and preventative behaviors. LPA identified five distinct profiles of people representing a combination of low and high uncertainty and low, moderate, and high risk perceptions. Results revealed that latent‐profile group membership predicted intention to interact with others outside of the household, intention to engage in non‐essential shopping, intention to attend an in‐person religious gathering, intention to wear a mask in public, and self‐reported physical distancing in the past week. Profile membership did not predict intentions to: dine out, go to the nail/hair salon, go to the gym, nor physically distance from others in the future, nor did it predict handwashing in the past week.